2012
DOI: 10.2220/biomedres.33.191
|View full text |Cite
|
Sign up to set email alerts
|

Structure-function relationship of the nuclear localization signal sequence of parathyroid hormone-related protein

Abstract: Parathyroid hormone-related protein (PTHrP) contains a nuclear localization signal (NLS) sequence within 87-107. NLS sequences are generally capable of penetrating cellular membranes due to a richness of basic amino acid residues, and thus have been used as cell-penetrating peptides (CPPs) to translocate biologically active peptides/proteins into cells. The NLS sequence of PTHrP is not exception to this finding; however, PTHrP(87-107) contains 2 acidic glutamate residues at 99 and 101 within the basic amino ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…This is the first amino acid of the osteostatin sequence (7,8), and it has also been included in the sequence constituting the NLS domain by most investigators (3,5,46,51) but not by others (19,20). We here show that deletion or mutation of this amino acid in the PTHrP molecule significantly hampers its stimulatory effects on MC3T3-E1 cell proliferation and several osteoblast differentiation markers, namely ALP activity and OC gene expression.…”
Section: Discussionmentioning
confidence: 70%
“…This is the first amino acid of the osteostatin sequence (7,8), and it has also been included in the sequence constituting the NLS domain by most investigators (3,5,46,51) but not by others (19,20). We here show that deletion or mutation of this amino acid in the PTHrP molecule significantly hampers its stimulatory effects on MC3T3-E1 cell proliferation and several osteoblast differentiation markers, namely ALP activity and OC gene expression.…”
Section: Discussionmentioning
confidence: 70%
“…However, a large number of ncNLS do not have a regular characteristic structure, including those of PTHrP (parathyroid hormone-related protein) [ 29 ], Pho4 (phosphorylation regulates association of the transcription factor) [ 30 ], and rpL23a (ribosomal protein L23a) [ 31 ], among others (Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…MPG is a fusion peptide of the HIV-1 gp41 derived sequence combined with the NLS of the SV40 large T antigen [20,21]. Also, NLS of PTHrP [37], NF-jB, TFIIE-b and OCT-6 showed cell membrane penetrating function [38]. In this study, the NLS of human cytokine IL-1a showed remarkable cell membrane penetrating ability in vitro and in vivo suggesting NLS could have cell membrane penetration ability.…”
Section: Discussionmentioning
confidence: 59%